Exploring sensitivity factors influencing technology adoption for climate change adaptation among agricultural communities of Kedah and Kelantan, Malaysia - Khalid, Nurul Amiera; Arif Shah, Jasmin; Mohamed Haris, Nur Bahiah; Burhan, Nik Ahmad Sufian; Mohamed Shaffril, Hayrol Azril; Abu Samah, Asnarulkhadi (HH Publisher, 2024)
The agricultural sector is exceptionally susceptible to fluctuations in climatic conditions, and such changes significantly impact agricultural productivity as well as the welfare of agricultural communities. Therefore, it is crucial to comprehend the vulnerability and risk of the agricultural communities to these effects. The agriculture ability of the sector to successfully adapt over the long term will depend heavily on the adoption of new technologies. Therefore, the adoption of emerging technologies into agriculture is a key component of climate change adaptation. Nguyen et al. (2021) suggest that it would be great for future study to conceptualize the integration of economic, social, and political issues in improving adaptation among agricultural communities. Therefore, current study attempts to determine social vulnerability of the agricultural communities particularly in terms of sensitivity which consist of economic, political, cultural and institutional factors that influence technology adoption for climate change adaptation. The study will be using questionnaire as the main research instrument. A descriptive, correlation and regression analysis will be employed in order to achieve the objectives of the study. A non-probability sampling known as convenient sampling technique will be employed as the sampling technique. The study will be conducted in Kedah and Kelantan as both states are predominantly characterized by an agriculture-based economy which currently have been reported to be affected by climate change. Results of the study will contribute to the making of policy related to agriculture and climate change adaptation as well as for future study related to the field.The agricultural sector is exceptionally susceptible to fluctuations in climatic conditions, and such changes significantly impact agricultural productivity as well as the welfare of agricultural communities. Therefore, it is crucial to comprehend the vulnerability and risk of the agricultural communities to these effects. The agriculture ability of the sector to successfully adapt over the long term will depend heavily on the adoption of new technologies. Therefore, the adoption of emerging technologies into agriculture is a key component of climate change adaptation. Nguyen et al. (2021) suggest that it would be great for future study to conceptualize the integration of economic, social, and political issues in improving adaptation among agricultural communities. Therefore, current study attempts to determine social vulnerability of the agricultural communities particularly in terms of sensitivity which consist of economic, political, cultural and institutional factors that influence technology adoption for climate change adaptation. The study will be using questionnaire as the main research instrument. A descriptive, correlation and regression analysis will be employed in order to achieve the objectives of the study. A non-probability sampling known as convenient sampling technique will be employed as the sampling technique. The study will be conducted in Kedah and Kelantan as both states are predominantly characterized by an agriculture-based economy which currently have been reported to be affected by climate change. Results of the study will contribute to the making of policy related to agriculture and climate change adaptation as well as for future study related to the field.